Program directors’ reflections on national policy change in medical education: insights on decision-making, accreditation, and the CanMEDS framework - Dore, Kelly; Bogie, Bryce James Mack; Saperson, Karen; Finlay, Karen; Wasi, Parveen (Canadian Medical Education Journal, 2021)
Background: Outcomes of national policy change impact all levels of the organizational hierarchy. The medical education literature is sparse on how reflections from program directors (PDs) on past large-scale policy changes can inform future policy initiatives. To fill this gap, we conducted a national survey on PDs’ perceptions of, and reflections on, decision-making in medical education, accreditation procedures, and the CanMEDS framework implementation. Methods: The survey was distributed to former Canadian specialty medicine PDs (N = 684). Descriptive analysis was performed on quantitative data, thematic analysis was performed on qualitative comments, and comparisons between the quantitative and qualitative findings were performed to identify areas of convergence and/or divergence. Results: A total of 265 (38.7%) former PDs participated. Quantitative analysis revealed that 52.8% of respondents did not feel involved in decision-making regarding policy changes, 45.1% of respondents did not feel prepared to assess the CanMEDS Roles, and PDs were divided on the reasonableness of accreditation documentation. Qualitative analysis produced four themes: communication, resources, expectations of outcomes, and buy-in. Nine sub-themes were also identified. A high level of convergence was identified across the content, with only four areas of divergence identified. Conclusions: Our findings have the potential to inform future policy and/or accreditation changes. Without the lens of those charged with overseeing the implementation, policy evaluation and quality improvement will remain uninformed. PDs, therefore, bring unique insights into our understanding of national policy changes, and without the voices of these frontline implementers, the true success of policy change implementation will be hindered.